Perilaku Pengelolaan Keuangan Keluarga: Peran Moderasi Pendapatan - Husna, Nur Af’idatul; Lutfi, Lutfi (Jurnal Samudra Ekonomi dan Bisnis, 2022)
Financial Management Behavior is crucial to achieve future financial well-being. The purpose of this research is to examine the influence of financial experience and financial knowledge on family financial management behavior with income as a moderating variable. The samples are 249 respondents who are married with a minimum income of Rp. 5.000.000,- per month and live in Surabaya. Data is analysed using Structural Equation Modeling. The results indicate that there are significant positive influences of financial experience and financial knowledge to family financial management behavior; there is no influence of income to family financial management behavior; and, income strengthens the influence of financial knowledge to family financial management behavior. This study suggests households to spend more money for pension fund programs and improve their financial knowledge, especially about investment and credit.